Trapped in a mesmeric dream state. A stody of the esoteric and fantastic elements in Carlos Fuentes' "Aura" - Arciello, Daniele (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This essay aims to analyse the most relevant esoteric and fantastic aspects in Aura by Carlos Fuentes. Despite the great amount of admirable study regarding this area of interest, the value of this work undoubtedly deserves more consideration to highlight its relevance in current issues. As a matter of fact, the protagonist of the tale takes a path that, keeping in line with what is typical for characters in traditional horror literature, is an effective allegory for the existential journey in the context of the struggle between the enlightenment of the rational being and the darkness of the inexplicable. The dichotomous conceptualisation of light and darkness is expressed by a non-mimetic narrative that combines itself with occultism and apotropaic rituals. In order to exhaustively analyse the ensemble of fantastic literary elements that undergird the text, we must delve deep into its contents. Our aim is to emphasise the captivating storyline of a writer capable of compelling both the reader and the main character to be dominated by the spell of the witch.
Keywords: Aura; Carlos Fuentes; esoterism; fantastic literature elements; twentieth century Spanish American Literature